Free-Spin Dominated Magnetocaloric Effect in Dense Gd3+ Double Perovskites - Koskelo, EliseAnne C.; Liu, Cheng; Mukherjee, Paromita; Kelly, Nicola D.; Dutton, Siân E. (Chemistry of materials, 2022)
Frustrated lanthanide oxides with dense magnetic lattices are of fundamental interest for their potential in cryogenic refrigeration due to a large ground state entropy and suppressed ordering temperatures but can often be limited by short-range correlations. Here, we present examples of frustrated fcc oxides, Ba2GdSbO6 and Sr2GdSbO6, and the new site-disordered analogue Ca2GdSbO6 ([CaGd] A [CaSb] B O6), in which the magnetocaloric effect is influenced by minimal superexchange (J 1 ∼ 10 mK). We report on the crystal structures using powder X-ray diffraction and the bulk magnetic properties through low-field susceptibility and isothermal magnetization measurements. The Gd compounds exhibit a magnetic entropy change of up to −15.8 J/K/molGd in a field of 7 T at 2 K, a 20% excess compared to the value of −13.0 J/K/molGd for a standard in magnetic refrigeration, Gd3Ga5O12. Heat capacity measurements indicate a lack of magnetic ordering down to 0.4 K for Ba2GdSbO6 and Sr2GdSbO6, suggesting cooling down through the liquid 4-He regime. A mean-field model is used to elucidate the role of primarily free-spin behavior in the magnetocaloric performance of these compounds in comparison to other top-performing Gd-based oxides. The chemical flexibility of the double perovskites raises the possibility of further enhancement of the magnetocaloric effect in the Gd3+ fcc lattices.